The implementation of the European Union water framework directive in Cyprus - Birol, Ekin; Koundouri, Phoebe; Remoundou, Kyriaki (Springer, 2011)
In this chapter, first the raison d'etre, aims and timeline of the WFD are introduced. Particular emphasis is given to the economic and social aspects of the WFD to assist policy makers towards sustainable water resource management and social welfare enhancement. This is followed by a summary of the relevant steps taken to date to implement the WFD. The potential challenges that Cyprus will face while impelmenting the Directive a re drawn to attention. The potential future social and economic benefits of the implementation of the WFD are examined. Finally, equity issues related to the different consumers' access to water, in the face of the Directive's requirment for full-cost recovery of water services, are discussed. As will be indicated in this chapter, the consecutive chapters in this book present more details on the impacts and challenges of, and issues related to the implemetation of the WFD in Cyprus.